PENGARUH MANAJEMEN HUBUNGAN PELANGGAN TERHADAP KEPERCAYAAN DAN KOMITMEN PADA SALON NEW YORK 1 MATARAM - Agusfianto, Nendy Pratama (Jurnal Magister Manajemen, 2015)
This study aims to (1) reveal the effect of customer relation management on customers’ commitments, (2) to find out the effect of customer relation management and customers’ trust, and (3) to uncover the effect of consumer trust on their commitment. This type of study belongs to associative research, which aims to investigate the relationship between two or more variables. The population in this study encompassed all the customers of New York 1 beauty salon in Mataram. Using Malhotra opinion model, the number of samples obtained was 65 people. The research data were collected through of use a questionnaire distributed to the a number of respondents, and the data analysis design employed for the purpose was path analysis. Results of the analysis based on path analysis were presented as follows (1) the management of customer relation management had no significant effect on the customers’ commitments, (2) the customer relation management had a significant and positive impact on the customers’ confidence, (3) the trust had a significant and positive effect on the customers’ commitment. Keywords : Customer Relation Management, Confidence, Commitment